Assessment of the effect of heat transfer intensifiers on the energy and mass efficiency of crystallizers - V. V. Chernyavskaya; V. B. Sapozhnikov; I. Yu. Golovanov; M. A. Ugolnikova (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. The aim of the study is to assess the presence and form of heat transfer intensifiers in a volumetric crystallizer of the "pipe in a pipe" design.Method. The study is based on the method of thermodynamic analysis, natural and computational modeling of processes using computer modeling.Result. It is shown that the most important parameter of heat exchangers (regardless of the process) is the amount of heat transferred per unit of time (thermal power, which is directly proportional to the surface area of the heat exchange). The article presents the results of evaluating the effect of the presence and form of heat transfer intensifiers on the mass of the Crystallizer and the power required for pumping the coolant (when freezing ice on the inner surface of the heat exchanger tube) based on the results of computer modeling.Conclusion. Two forms of heat transfer intensifiers providing the best energy and mass efficiency of crystallizers are presented.